Caribbean regional financial stability report 2015- (Caribbean Centre for Money and Finance, UWI St AugustineTT, 2016)
Aims to sensitise the main regional financial stability stakeholders, including the regional public, of issues relevant to the stability of the financial system in the region. Reviews the main sources of risks to the stability of the regional financial system, as well as the policy measures being used to deal with emerging risks to help build confidence and provide policymakers with guidance on the building blocks to defuse any financial tensions in the system. Identifies the need for financial sector reforms, with an emphasis on increased harmonisation, coordination and cooperation from a regional perspective.
Keywords: FINANCIAL MANAGEMENT